Сокровища Валькирии: [роман] / Сергей Алексеев - Алексеев Сергей Трофимович (Русский проект, 1997)
Экземпляры: ф.2 (2003) / Инвентарный номер: 44723 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44